Cyberbullying behavior: A study of emotional maturity Yogyakarta students - Chornelius Hutagaol (Journal of Advanced Guidance and Counseling, 2021)
Purpose -  The research objective was to determine the relationship between emotional maturity and cyberbullying behavior among students.Method - This research is a case study using a quantitative method based on a post-positivism approach. The sampling technique in this study using purposive sampling technique. The number of subjects in this study amounted to 60 students. The data analysis technique used product moment correlation.Result - The results of the research analysis using the "product moment" correlation technique showed a correlation number of -0.720 (p 0.01). The correlation coefficient value shows -0.720 which means that it has a very strong relationship level. Thus, the higher the emotional maturity, the lower the cyberbullying behavior, and the lower the emotional maturity, the higher the cyberbullying behavior.Implications – To define university-Students are included in the early adulthood stage which should have good emotional maturity. High emotional maturity allows individuals to have the ability to understand reality and facts and the quality of responding to situations by separating pressure and attraction for pleasant and unpleasant feelings.Originality - This research is cyberbullying behavior study using a quantitative method based on a post-positivism approach.***Tujuan -  Penelitian ini bertujuan untuk mengetahui hubungan antara kematangan emosi dengan perilaku cyberbullying pada mahasiswa.Metode - Penelitian ini merupakan studi kasus dengan menggunakan metode kuantitatif dengan pendekatan post-positivisme. Teknik pengambilan sampel dalam penelitian ini menggunakan teknik purposive sampling. Jumlah subjek dalam penelitian ini berjumlah 60 siswa. Teknik analisis data menggunakan korelasi product moment.Hasil - Hasil analisis dengan teknik korelasi product moment menunjukkan angka korelasi sebesar -0,720 (p0,01). Nilai koefisien korelasi menunjukkan -0,720 yang berarti memiliki tingkat hubungan yang sangat kuat. Dengan demikian, semakin tinggi kematangan emosi maka semakin rendah perilaku cyberbullying, dan semakin rendah kematangan emosi maka semakin tinggi perilaku cyberbullying.Implikasi - Untuk mendefinisikan mahasiswa termasuk dalam tahap dewasa awal yang harus memiliki kematangan emosi yang baik. Kematangan emosi yang tinggi memungkinkan individu memiliki kemampuan untuk memahami realitas dan fakta serta kualitas dalam merespon situasi dengan memisahkan tekanan dan ketertarikan terhadap perasaan menyenangkan dan tidak menyenangkan.Originalitas - Penelitian ini merupakan penelitian perilaku cyberbullying dengan menggunakan metode kuantitatif dengan pendekatan post-positivisme.